Transfer of Ownership in State Retail Sukuk: Shariah Review Based on DSN-MUI Fatwa and AAOIFI Sharia Standards - Nugroho, Joko; Darwanto, Agus (Suhuf: International Journal of Islamic Studies, 2025)
Underlying Assets of Retail State Sukuk are State Property which in reality cannot be easily transferred. Although the DSN-MUI has given an opinion on the suitability of the Retail State Sukuk contract with Islamic law, the DSN-MUI fatwas do not broadly regulate the Underlying Assets of Sukuk. The issuance of the Exposure Draft of Shari'ah Standard No. 62 on Sukuk by the Accounting and Auditing Organization for Islamic Financial Institutions (AAOIFI) on November 6, 2023 will have an impact on the sukuk industry that is given asset collateral because it requires a real transfer of ownership of the Underlying Asset to investors. This study will complement the discussion regarding the suitability of sharia for the Underlying Assets of Retail State Sukuk from the perspective of the DSN-MUI fatwa, AAOIFI Sharia Standards, and the similarity of sale and purchase approaches. This study uses a qualitative research method. Primary data is taken directly from the official publication of sukuk from the Government. The results of this study can be summarized as follows. Underlying Assets of Retail State Sukuk are State Property (BMN) that do not experience a transfer of ownership. Based on DSN-MUI fatwas, Retail State Sukuk does not conflict with sharia. The provisions of Underlying Assets of Retail State Sukuk do not meet AAOIFI Standards because there is no transfer of ownership from the Government to investors. The Underlying Asset Contract of Retail State Sukuk has several similarities with the al-Wafa' contract which is prohibited by the majority of scholars because it is not free from usury.